THE ANALYSIS OF FINANCIAL STATEMENTS TO ASSESS THE PERFORMANCE OF PT. BANK PERKREDITAN RAKYAT NUSA UTARA - Wongkar, Yessi Devika; Mawikere, Lidia M. (Universitas Sam Ratulangi, 2015)
BPR is a bank conducting conventional business andÂ based on sharia their activities do not provide services in payment traffic. This study aims to determine the effect of financial statements in assessing the financial performance at PT. Bank BPR Nusa Utara Manado. The method used is descriptive, testing is done using the ratio of liquidity, solvency and profitability in the financial statements for 2012-2014. The results shows the performance of BPR assessed on bank liquidity ratio in 2014 indicates the position and financial performance are increasingly efficient. The bank's solvency ratio in 2012 shows primary bank experiencing adverse conditions because the rate of bank loans is quite high but can be covered by the bank's capital. Overall the Profitability of bank is in good condition, especially in Gross profit margin, ROA also stable condition, well between the load with the income received, indicating that the bank is in a state of good performance. Bank management should pay attention to the relationship between the level of liquidity and efficiency of their operations and the level of profitability (profit enterprises) to be achieved by the bank. Keywords: liquidity ratios, solvency ratios, profitability ratios